2013
DOI: 10.4192/1577-8517-v13_4
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Computing: How does it differ from IT outsourcing and what are the implications for practice and research?

Abstract: Abstract. The purpose of this paper is to provide an evolutionary perspective of cloud computing (CC) by integrating two previously disparate literatures: CC and information technology outsourcing (ITO). We review the literature and develop a framework that highlights the demand for the CC service, benefits, risks, as well as risk mitigation strategies that are likely to influence the success of the service. CC success in organisations and as a technology overall is a function of (i) the outsourcing decision a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
6
0
3
Order By: Relevance
“…In addition to the IS success model perspective, previous studies indicate that cloud computing adoption is usually a kind of IS outsourcing. 12 For hospitals, transitioning from traditional IS platform to a cloud computing environment is a large-scale transformation. Most hospitals will look to collaborate with professional third-party cloud service providers.…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
“…In addition to the IS success model perspective, previous studies indicate that cloud computing adoption is usually a kind of IS outsourcing. 12 For hospitals, transitioning from traditional IS platform to a cloud computing environment is a large-scale transformation. Most hospitals will look to collaborate with professional third-party cloud service providers.…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
“…SMEs use cloud computing because of reduced expenses; concentration on core competencies; efforts to improve business processes; the requirements of accessing technology, experts and skills; versatility; enhancement; and political reasons (Lacity et al, 2009). The key reasons for the SMEs to outsource their IT operations are to reduce cost, limit their investments on IT and reduce the risk of not being competitive, and as a tool in managing task overload during peak seasons (Yigitbasioglu et al, 2013). Previous studies identified other advantages of cloud computing as follows:…”
Section: Cloud Computingmentioning
confidence: 99%
“…Esta tecnología ha sido estudiada como un nuevo modelo de negocio (Ross y Blumenstein, 2013;Leimeister et al, 2010, Marston et al, 2011, Yigitbasioglu et al, 2013 que permite mayor capacidad de almacenamiento, facilidad de acceso y uso de recursos o ahorro de costes. Además, los usuarios de la nube se benefician de un más adecuado uso de los recursos, en cuanto a eficiencia, flexibilidad y transferencia de riesgos (Armbrust et al, 2010).…”
Section: C Tecnología (Edición 22) Vol6 -Nºunclassified